PLAN DE NEGOCIOS PARA LA IMPLEMENTACIÓN DE PRODUCTOS TURISTICOS EN LA FINCA “LUZÓN” DE LA PARROQUIA PURUNUMA, CANTÓN GONZANAMÁ, PROVINCIA DE LOJA - Cueva Luzón, Ana Stefania (2019)
In the Purunuma parish belonging to canton Gonzanamá, tourism is an undeveloped activity, and in this scenario the "Luzón" farm is evident, a place that has great scenic beauty as well as engaging in different agricultural activities, for this reason, the present research work, emerged with the initiative to enter the tourism market in order to promote local development and determine the viability of implementing tourism products in the area. The development of this proposal has as a general objective: Prepare a business plan for the implementation of tourism products in the "Luzón" farm of the Purunuma parish, Gonzanamá canton, province of Loja, and for its fulfillment three specific objectives were established: tourist diagnosis of the current situation of the "Luzón" farm of the Purunuma parish, which allowed to know the internal and external situation of the farm; propose the business plan for tourism products in the "Luzón" farm of the Purunuma parish, Gonzanamá Canton, Loja Province, the business definition was made; propose strategies for the implementation of the Business Plan for tourist products in the "Luzón" farm of the Purunuma parish, Gonzanamá Canton, Loja Province, where the viability of the project was known through financial analysis. To meet the specific objectives of the research, descriptive, analytical, inductive and deductive methods were used, which helped to select and analyze the information obtained. The inventory and ranking hierarchy of attractions of the Ministry of Tourism were used. Regarding techniques, the interview, survey and direct observation were used, in order to elaborate an internal and external analysis of the farm, and the SWOT matrix, which allowed to establish strategies for the implementation of tourism products in the estate. It was determined that the farm is a place that has resources and potential tourist attractions for tourism, in addition it was determined that the business plan has an initial investment for its execution of $ 164,178.08. and from the technical, administrative and financial point of view the project is viable and profitable.